Share-review-practise spiral model (SRP) to enhance postgraduate students' cognitive skills - Atichart Harncharnchai (2018)
To achieve a master's degree in Knowledge Management, critical thinking and analytical skills are required to develop clarity and rigor in reasoning and the ability to understand and evaluate the reasoning of others' paper work. However, most graduate students in Thailand who are familiar with lecture-based approach lack such skills which are the key obstacles to learning process. This paper proposes a Share-Review-Practise Spiral Model (SRP) for learning enhancement with the integration of the SECI model, Communities of Practice (CoPs) and After Action Review (AAR) as a new learning paradigm which aims to bring up master's degree students' cognitive skills. Four stages consisting of, firstly, socialization in virtual communities of practice helps acquire necessary 'content knowledge' and become active members. Then, informal after action review (AAR) is used to analyze the content knowledge and transform into 'lessons-learned knowledge'. Next, face-to-face discussion combining with lecturer's guidance help students crystallize their lessons-learned knowledge and transform into 'critical knowledge'. The final stage is applying critical knowledge into practice of individual problem-solving case. To see students' cognitive skill improvement, such activities are repeated and assessed. Target group is postgraduate students taking the theoretical foundations of knowledge management course at Chiang Mai University, Thailand. The implementation took approximately 30 hours over 4 weeks. Findings are i) the relationships of social network among students within the CoPs are strong while two nodes show the highest degree centrality of 26 and 23, ii) students' critical thinking and analytical skills improve after they participating in CoP over time; iii) students' understanding ability and applying skills have a tendency of improvement through individual problem-solving and iv) only a few number of students can shift their cognitive skills from basic level of understanding and applying to higher level of analysis. Furthermore, the result also reveals that the SRP helps change students' behavior shifting from spoon-feeding to self-feeding manner.